Developing an Energy Efficient Urban Transport Plan for Zarqa City Downtown Area - World Bank (Washington, DC, 2014)
To promote energy efficiency in the delivery of city services, the Energy Sector Management Assistance Program (ESMAP) in the World Bank launched a multi-year initiative, the Energy Efficient Cities Initiative (EECI), in December 2008 to help scale-up energy efficiency improvements in developing country cities around the world. One of the tools to help scale up energy efficiency improvements under the EECI program is the provision of pre-investment policy support wherein ESMAP applies its expertise in advising cities on appropriate analytical tools, policy and regulatory framework, lifecycle costing principles, energy efficient codes, and financing schemes. ESMAP is also working with Cities Alliance City Development Strategies (CDS) in this regard. Within this context and in keeping with the Government of Jordan's (GOJ) regional development agenda, ESMAP received a proposal from the Zarqa Municipality seeking technical and financial support for developing an energy efficient urban transport planning strategy for the city Downtown area. This is linked with the cities alliance grant to prepare inputs to the broader CDS for preparation of the new Zarqa master plan to be developed by the Ministry of Municipal Affairs (MOMA).